AN ANTHOLOGY OF THE DISTINGUISHED ACHIEVEMENTS IN SCIENCE AND TECHNIQUE. PART 49: AIRCRAFT DESIGNER OLEG ANTONOV AND HIS ACCOMPLISHMENTS IN AIRPLANE DESIGN - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2019)
Purpose. Preparation of short scientifically-historical essay about one of founders of domestic aircraft design, prominent Ukrainian aircraft designer O.K. Antonov. Methodology. Known scientific methods of collection, analysis and analytical treatment of scientific and technical information, touching becoming and development of Soviet aviation and resulted in scientific monographs, journals and internet reports. Results. A short scientifically-historical essay is resulted about the prominent Ukrainian aircraft designer Oleg Konstantinovich Antonov, becoming one of founders of Soviet military cargo and civil aviation. Basic scientific and technical achievements of the glorified aircraft designer O.K. Antonov are indicated and team of headed them in the period of 1952-1984 of legendary Design Bureau 473 (Kyiv) in area of aircraft design, bringing a domestic aviation around to world heights. Basic tactical and technical descriptions are described created under his scientific and technical guidance of such types of passenger airplanes known in the world as An-2, An-10 and An-24, and also troop-carriers of type An-12, An-22 «Antaeus», An-26, An-30, An-32, An-72 and An-124 «Ruslan». Short information is resulted about tactical and technical descriptions of the largest in the world of heavy distant turbo-jet military cargo airplane type An-225 «Mriya», created in 1980-th years in Design Bureau named after O.K. Antonov. It is marked that under scientific and technical guidance of aircraft designer O.K. Antonov in the former USSR about 100 types of aircrafts of the military and civil aircrafts were developed and created. It is pointed out that Doctor of Technical Sciences, Academician of the Academy if Sciences the Ukrainian SSR and of the Academy of Sciences the USSR became a founder acknowledged in the world of Ukrainian aviation scientific school. Information, touching common to all mankind qualities of this great aircraft designer, is resulted, and also handed O.K. Antonov for merits before Homeland of governmental rewards, bonuses and other insignia, underlining his prominent contribution to development of domestic aircraft construction. Originality. Certain systematization is executed known from scientific journals and other mass of scientific and technical materials media, touching becoming and development in the period of 20-21-th centuries of Soviet aviation and ponderable scientific and technical contribution to the military and civil aircraft design of the prominent Ukrainian aircraft designer O.K. Antonov. Practical value. Scientific popularization and deepening for the students of higher school, engineering, technical and scientific workers of scientific and technical knowledge in area of history of becoming and development of Soviet aircraft design, extending their scientific and technical range of interests and further development of scientific and technical progress in society.